High miR-454-3p expression predicts poor prognosis in hepatocellular carcinoma - Li, Yanqing (Cancer Manag Res, 2019)
Purpose: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the clinic all over the world, which has become a public health challenge. The T/N/M staging system plays a core role in HCC prognosis. However, it cannot precisely stratify the risk of HCC prognosis. MiR-454-3p plays an important role in the progression of tumors. Therefore, we need to develop more reliable prognostic markers for HCC patients which can focus on miR-454-3p. Methods: We used Chi-square and Fisher exact tests to assess correlations between miR-454-3p expression and clinical parameters in liver cancer patients from The Cancer Genome Atlas database (TCGA). Then, Cox regression analysis, Kaplan-Meier curve, and log-rank test were used to compare the difference of survival between the high-expression group and low-expression group, and P value was included. Finally, we used TCGA data set to carry out gene enrichment analysis. Results: In this research, the expression of miR-454-3p increased in HCC and was associated with patient survival, G3/G4 staging, III/IV staging and T staging. Higher miR-454-3p expressed patients had shorter survival time. Besides, mitotic spindle, G2M checkpoint, and E2F targets were differentially enriched in miR-454-3p high-expression phenotype by Gene set enrichment analysis. Conclusion: Overexpression of miR-454-3p may be a significant and independent predictor of poor prognosis in HCC patients.